Thank you, Meiling - Talley, Linda, 1948-; Maeno, Itoko (Kansas City, Mo. : MarshMedia, 1999)
An ill-mannered duck learns how to be courteous on a trip to the market with a Chinese boy who is buying moon cakes and lanterns to celebrate the Mid-autumn (Moon) Festival; includes information about the phases of the moon, Chinese history and culture, and the Moon Festival.
4.3
K-3
Keywords: Mid-autumn Festival -- Fiction; Conduct of life -- Fiction; Ducks -- Fiction; China -- Fiction; Mid-autumn Festival -- Fiction; Conduct of life -- Fiction; Ducks -- Fiction; China -- Fiction